(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study explores employee awareness and attitudes towards cybersecurity technologies. As organizations strive to improve their cybersecurity measures, the human element remains a critical yet often overlooked factor. This research investigates the correlation between employee awareness and the adoption of emerging cybersecurity technologies, the impact of these technologies on cybersecurity incident rates, and the relationship between employee satisfaction and cybersecurity awareness. A qualitative exploration approach was employed, utilizing data from peer-reviewed publications, technology conference proceedings, and industry reports. Surveys of cybersecurity experts and organizational executives were conducted to identify recurring themes and concerns. The findings reveal that increased employee awareness significantly enhances the effectiveness of cybersecurity measures and reduces security incidents. Furthermore, the study highlights the necessity of continuous training and education for employees to maintain a robust cybersecurity posture. The research also emphasizes the importance of integrating cybersecurity technologies into daily operations to enhance their efficacy. This comprehensive examination aims to assist organizations in developing resilient cybersecurity strategies that address both technological and human factors.